Xq25 duplication: the crucial role of the STAG2 gene in this novel human cohesinopathy. Issue 1 (5th March 2015) - Leroy, C.; Jacquemont, M.‐L.; Doray, B.; Lamblin, D.; Cormier‐Daire, V.; Philippe, A.; Nusbaum, S.; Patrat, C.; Steffann, J.; Colleaux, L.; Vekemans, M.; Romana, S.; et al.
Abstract : The Xq25 duplications syndrome has recently emerged as a distinct clinical entity. We report here on six new patients belonging to two unrelated families and harbouring an Xq25 microduplication detected by array CGH. Similarly to previously reported cases, the phenotype of our patients is characterized by delayed milestones, speech disturbance, intellectual disability, abnormal behaviours and a characteristic facial dysmorphism. The common duplicated interval allowed further refinement of the shortest region of overlap to 173 kb, including only one gene, STAG2, which encodes a component of the cohesin complex. We suggest that increased STAG2 gene copy number and dysregulation of its downstream target genes may be responsible for the specific clinical findings of this syndrome. Therefore, the Xq25 microduplication could be considered as a novel cohesinopathy, thus increasing the group of these disorders.